2019
DOI: 10.3390/molecules24061105
|View full text |Cite
|
Sign up to set email alerts
|

The Antidepressant-like Effect of Flavonoids from Trigonella Foenum-Graecum Seeds in Chronic Restraint Stress Mice via Modulation of Monoamine Regulatory Pathways

Abstract: Fenugreek (Trigonella Foenum-Graecum) seeds flavonoids (FSF) have diverse biological activities, while the antidepressant-like effect of FSF has been seldom explored. The aim of this study was to evaluate the antidepressant-like effect of FSF and to identify the potential molecular mechanisms. LC-MS/MS was used for the determination of FSF. Chronic restraint stress (CRS) was used to establish the animal model of depression. Observation of exploratory behavior in the forced swimming test (FST), tail suspension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 54 publications
4
21
0
Order By: Relevance
“…The extract also inhibited MAO-A activity as well as downregulating the KLF11, SIRT1, and MAO-A protein expression levels in the PFC and hippocampus. These results justify the role of flavonoids in the antidepressant-like effects of this species [364]. Uncaria lanosa var.…”
Section: Dosesupporting
confidence: 77%
“…The extract also inhibited MAO-A activity as well as downregulating the KLF11, SIRT1, and MAO-A protein expression levels in the PFC and hippocampus. These results justify the role of flavonoids in the antidepressant-like effects of this species [364]. Uncaria lanosa var.…”
Section: Dosesupporting
confidence: 77%
“…Additionally, the activities of different neurotransmitters have also been influenced in a positive way such as decreased MAO activity. [39] These studies support the evidence that fenugreek compounds possess momentous neuroprotective effect.…”
Section: Fenugreek Against Neurological Disorderssupporting
confidence: 64%
“…A recent study has also shown significant improvement among postmenopausal discomforts when supplemented with 250 mg × 2/day of FHE for 42 days (unpublished data, communicated). Another study states that fenugreek seed flavonoids exhibit an antidepressant‐like effect by downregulating the KLF11/SIRT1‐MAO‐A pathway, inhibiting MAO‐A expression and activity, as well as upregulating monoamine neurotransmitters levels (Wang et al., 2019).…”
Section: Discussionmentioning
confidence: 99%